Haemophilus infection in cystic fibrosis. Issue 3 (March 1990) - Rayner, R J; Hiller, E J; Ispahani, P; Baker, M
Abstract : Twenty seven patients with cystic fibrosis under the age of 12 years and 27 matched patients with asthma were followed up in a prospective study for one year. The isolation rate of non-capsulated strains of Haemophilus influenzae from cough swabs and sputum specimens taken at routine clinic visits every two months was significantly greater in cystic fibrosis than in asthma. Haemophilus para-influenzae was equally common in both groups. During exacerbations the isolation rate of H influenzae in cystic fibrosis was significantly greater than at other times, whereas in asthma there was no significant difference. The distribution of biotypes of H influenzae and H parainfluenzae was similar in the two groups. In cystic fibrosis, biotype I was associated with exacerbations. Biotype V was more common than in previous studies, but was not associated with exacerbations.